Cloud/web mapping and geoprocessing services - Intelligently linking geoinformation - Veenendaal, Bert; Brovelli, M.; Wu, L. (Elsevier BV, 2016)
We live in a world that is alive with information and geographies. ‘‘Everything happens somewhere” (Tosta, 2001). This reality is being exposed in the digital earth technologies providing a multidimensional, multi-temporal and multi-resolution model of the planet, based on the needs of diverse actors: from scientists to decision makers, communities and citizens (Brovelli et al., 2015). We are building up a geospatial information infrastructure updated in real time thanks to mobile, positioning and sensor observations. Users can navigate, not only through space but also through time, to access historical data and future predictions based on social and/or environmental models. But how do we find the information about certain geographic locations or localities when it is scattered in the cloud and across the web of data behind a diversity of databases, web services and hyperlinked pages? We need to be able to link geoinformation together in order to integrate it, make sense of it, and use it appropriately for managing the world and making decisions.